A simple estimation of glomerular filtration rate in children - Syarifuddin Rauf; Husein Akbar (Paediatrica Indonesiana, 2002)
Background The estimation of glomerular filtration rate (GFR) is routinely used in the assessment of renal function in children. An accurate measurement of GFR is very helpful in detecting renal disease.Objective The aim of this study was to compare GFR calculated by Schwartz's formula and that assessed by creatinine clearance measurement.Methods A study to evaluate GFR calculated by the Schwartz's fonnula and by the conventional creatinine clearance method was done on 114 (57%) boys and 86 (43%) girls aged 6-13 years hospitalized in the Department of Child Health, Hasanuddin University, Wahidin Sudirohusodo Hospital, Makassar in 1996.Results This study showed that there was no significant difference between the value of GFR determined by the conventional creatinine clearance method and that calculated by the Schwartz's fonnula according to age and sex. Our findings also did not show any Â difference of GFR assessed by both methods according to nutritional status of children. In regard to the accuracy of Schwartz's fonnula, the sensitivity, specificity, positive, and negative predictive values were 87.5%, 98.86%, 9 1.3%, and 98.3%, respectively.Conclusion It seems that Schwartz's fonnula might be used for assessing GFR in children particularly if either there is no facility for measuring creatininuria or there is difficulty in collecting complete and accurate-timing urine samples. The formula is a very simple and inexpensive method for determining GFR in children compared to the conventional creatinine clearance method.Â